INCLUSION OF CIDR IN OVSYNCH PROTOCOL TO IMPROVE FERTILITY IN POSTPARTUM SUBESTRUS BUFFALOES - KUMAR, K RAVI; ASOKAN, S A; VEERAPANDIAN, C (The Indian Journal of Animal Reproduction, 2023)
Twenty four postpartum subestrus buffaloes not showing observed estrus within 60 days after calving were randomly and equally divided into ovsynch-subestrus and ovsynch plus CIDR-subestrus groups. Ovsynch-subestrus group buffaloes were subjected to ovsynch protocol which consisted of 100 μg i.m. injection of GnRH on the day of start of synchronization (d O), 25 mg i.m. injection of PGF211 seven days later (d 7), another 100 μg i.m. injection of GnRH 48 h after PGF211 (d 9) and timed insemination 16 to 18 h after second GnRH injection (d 10). Ovsynch plus CIDR-subestrus buffaloes were subjected to ovsynch plus CIDR protocol which included intra vaginal placement of CIDR device for a period of 7 days starting from first GnRH injection ( d O) to PGF 211 injection d 7) for synchronization of ovulation. Blood samples were collected from all experimental animals on d -1 O and d 0, d 7, and d 9 days after insemination for the estimation of progesterone. During the treatment protocol none of the buffaloes exhibited visible premature estrus signs. However progesterone estimation showed that 25 per cent had exhibited premature estrus. The estrus detection rates were 41.66 and 58.33 per cent in ovsynch-subestrus and ovsynch plus CIDR-subestrus respectively. Most buffaloes showed i.ntermediate signs of estrus. The ovulatory response and first service conception rates were 83.33 and 33.33 and 100 and 41.66 per cent in ovsynch-subestrus and ovsynch plus CIDR-subestrus groups respectively.